Surgical prophylaxis with handwashing and its microbiological aspects: a literature review (Research, Society and Development, 2023)
Introduction: Surgical prophylaxis with hand washing is something well established in the academic and medical community, in view of its beneficial consequences in preventing contamination by microorganisms. hands in the surgical site, demonstrating the microbiological aspects and contributing to the knowledge about the antiseptics of the normal and transitory microbiota. Method: This is a bibliographical review research, carried out online in the Virtual Health Library, using the LILACS and SCIELO Databases, for the construction of the study. Results: It was analyzed and proven through bibliographical research that hand washing as a prophylaxis in the surgical environment is one of the most effective ways in this action. 2%, iodophors, solution containing hydrogen peroxide, glycerol and iodine and triclosan that are described in their microbiological specificities. preoperatively, however, the method that proved to be the most efficient for providing a safer and more suitable environment for the surgical patient was the use of alcoholic antiseptic solutions, since the mechanism of action of these antiseptics is linked to their bactericidal property